DESAIN JARINGAN BACKBONE KABEL OPTIK PADA PROVINSI KEPULAUAN RIAU DENGAN MENGGUNAKAN TEKNOLOGI DWDM - OTN - Situmorang, Saut; Azarya (LPPM ISTP, 2025)
In designing the Riau Island Network backbone province, it uses Dense Wavelength Division Multiplexing (DWDM) and Optical Transport Network (OTN) which cover 7 city districts consisting of 13 segments of 7 DWDM OTN and none Optical Land Amplifier (OLA) sites. From the design and backbone network simulation results, it was found that the value of Optical Link Power Budget (OLPB) < 50 dBm, where this is an ideal value for deploying a DWDM OTN backbone network, and the range of values for Optical Signal Noise Ratio (OSNR) ranges from 20 dBm < OSNR < 40, and also have an ideal Optical Rise Time Budget (ORTB) value < 60 ps dBm, which is the ideal value of OSNR, and also has a margin segment system > 7 dB